Listeriosis in infants: Prospective surveillance studies in Canada and Switzerland. Issue 7 (19th June 2021) - Abu-Raya, Bahaa; Jost, Marianne; Bettinger, Julie A; Bortolussi, Robert; Grabowski, Janet; Lacaze-Masmonteil, Thierry; Robinson, Joan L; Posfay-Barbe, Klara M; Galanis, Eleni; Schutt, Elizabeth; Mäusezahl, Mirjam; Kollmann, Tobias R
Abstract: Objectives: International data on listeriosis during infancy from large populations are essential to guide evidence-based empiric antibiotic guidelines for sepsis in infancy. We aimed to determine the incidence, clinical manifestations, and outcome of listeriosis in infants <6 months of age in Canada and Switzerland. Methods: Prospective, active surveillance of listeriosis in infants <6 months of age was conducted through the Canadian Paediatric Surveillance Program (May 2015 to April 2017) and the Swiss Paediatric Surveillance Unit (April 2017 to March 2018). Confirmed and probable cases were included. Results: In Canada, eight sporadic listeriosis cases were reported (incidence, 1.1/100, 000 live births/year). In Switzerland, four cases were reported (incidence, 4.5/100, 000 live births/year) of which three were part of a confirmed outbreak with an unclear source. In the two countries, eight of the 12 cases (66.6%) presented as early-onset disease (within the first 7 days of life) and none presented after 28 days life. Conclusions: Neonatal listeriosis is rare. Infants presenting with sepsis, especially after 4 weeks of life, may not routinely require empiric antibiotic coverage for listeriosis. Outbreak-related cases still occur. Continued surveillance is important.